2015
DOI: 10.1186/s12905-015-0228-8
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual patterns and disorders among secondary school adolescents in Egypt. A cross-sectional survey

Abstract: BackgroundTo our knowledge, no large population – based studies have been performed on the topic of menstrual patterns among Egyptian adolescent in recent years. The aims of this study were to identify menstrual patterns and associated disorders as well as the sources of menstrual health knowledge among Egyptian adolescents.MethodsA cross-sectional survey. A total of 800 questionnaires were administered to post-menarcheal Egyptian adolescents attending secondary schools in Giza, Egypt, from September 1, 2012, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
45
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 22 publications
7
45
1
4
Order By: Relevance
“…[28] Among those with dysmenorrhea, most common medications used were NSAIDs, followed by herbal preparations. Though the most commonly used method, NSAID use in this population was lower than that reported in an Australian study [5] .The pattern of medication use, both herbal and conventional ,is converse to that reported from Ethiopia [27] where more than sixty percent of the respondents use home remedies as a primary management option followed by NSAIDs.…”
Section: Discussioncontrasting
confidence: 71%
“…[28] Among those with dysmenorrhea, most common medications used were NSAIDs, followed by herbal preparations. Though the most commonly used method, NSAID use in this population was lower than that reported in an Australian study [5] .The pattern of medication use, both herbal and conventional ,is converse to that reported from Ethiopia [27] where more than sixty percent of the respondents use home remedies as a primary management option followed by NSAIDs.…”
Section: Discussioncontrasting
confidence: 71%
“…Previous research have reported a wide range of PMS prevalence in various countries from 12% in France to 98% in Iran [6]. In the surrounding countries, PMS prevalence was found to be 35.6% in Saudi Arabia among medical students [19], 65% in Egypt among adolescents [20], and 72.1% in Turkey among Medical students [17]. Choi, et al [21] indicated a PMS prevalence of 98.6%, 32.1% and 2.8% in a sample of students whose fathers have no income were more likely to have PMS.…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, the age of menarche is between 11-16, with a mean age of 13 year [9]. In our study, the mean age of first menstruation was 13.07±1.07 (10)(11)(12)(13)(14)(15)(16)(17) years. Of the participants, 66.5% expressed that cold weather increased their premenstrual complaints and 15.9% of them expressed that family problems increase complaints.…”
Section: Discussionmentioning
confidence: 48%
“…This difference can be attributed to the use of nonstandard scales for research and also by the varying characteristics of study participants, such as age, profession, education level, and sect. Abdelmoty et al declared that dysmenorrhea was the most prevalent (93%) menstrual disorder, followed by PMS (65%) and abnormal cycle lengths (43%), in their study of secondary school adolescents in Egypt [16].…”
Section: Discussionmentioning
confidence: 98%